The Effect of SiC Addition on AlNi Compact Mechanical Properties Produced Via Powder Metallurgy (Journal of University of Babylon for Engineering Sciences, 2019)
This research directed to produce Al-Ni alloys by powder metallurgy technique since of its marketable and industrial significant. Nickel and aluminum powders were determined their particle size then the powders mixed and blended with percent (Al - 20% Ni). Silicon carbide particles (SiC) powder supplemented to master alloy powder by percent (4-6- and 8 wt. %) separately then these powders mixed to obtain homogeneous distribution, then the powders compacted in cold pressure at 700 MPa. The sintering procedure was performed at (530°C) for 8 hrs. At vacuum atmosphere (10-4 torr). After cooling these samples grinded and polished to estimate microstructure, density, porosity, LOM, SEM, EDS, X-ray diffraction ,hardness and wear tests at dissimilar circumstances. Results showed that the hardness increased by (52%) and wear rate decreased by (55%) at 8 wt % silicon carbide addition, and it was the best results.